2019
DOI: 10.1186/s13071-019-3403-1
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative proteomic analyses of Schistosoma japonicum eggs and egg-derived secretory-excretory proteins

Abstract: Background Schistosome parasites lay up to a thousand eggs per day inside the veins of their mammalian hosts. The immature eggs deposited by females against endothelia of venules will embryonate within days. Approximately 30% of the eggs will migrate to the lumen of the intestine to continue the parasite life-cycle. Many eggs, however, are trapped in the liver and intestine causing the main pathology associated with schistosomiasis mansoni and japonica, the liver granulomatous response. Excretory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 62 publications
2
35
0
Order By: Relevance
“…Researchers found that glycoproteins such as IPSE (SmEP-25) [42], omega-1 [43], and kappa-5 [44] secreted by S. mansoni eggs and Sm29 [45] secreted by S. haematobium stimulate Th2 cytokine production in mice. For S. japonicum , egg secretory proteins (ESP) instead of IPSE, omega-1, and kappa-5 played a central role in driving the development of the immune response to the Th2 pattern because it was predicted to stimulate the production of IL-1, IL-3, IL-5, IL-4, and IL-13 [46]. Th2 response is supported by alternatively activated antigen presenting cells (APCs).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that glycoproteins such as IPSE (SmEP-25) [42], omega-1 [43], and kappa-5 [44] secreted by S. mansoni eggs and Sm29 [45] secreted by S. haematobium stimulate Th2 cytokine production in mice. For S. japonicum , egg secretory proteins (ESP) instead of IPSE, omega-1, and kappa-5 played a central role in driving the development of the immune response to the Th2 pattern because it was predicted to stimulate the production of IL-1, IL-3, IL-5, IL-4, and IL-13 [46]. Th2 response is supported by alternatively activated antigen presenting cells (APCs).…”
Section: Discussionmentioning
confidence: 99%
“…(3) A limited number of schistosome molecules have been investigated for potential in treating autoimmune and inflammatory diseases. In-depth transcriptomic and proteomic analysis of the different schistosome species and/or different developmental stages, such as egg secretome studies which have led to the discovery of highly sensitive antigens for the diagnosis of schistosomiasis ( 131 135 ) may facilitate the identification of additional molecules with therapeutic potential. An increasing number of candidates applicable for therapy purpose have been identified from other helminths ( 136 ), specific examples being anti-inflammatory protein-2 (AIP-2) from hookworm ( 137 ) and EgKI-1, a potent Kunitz type protease inhibitor from Echinococcus granulosus ( 126 ); on this basis, one could speculate that the schistosome orthologs of these molecules would likely elicit similar therapeutic effects.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…A recent proteomic analysis of schistosome eggs lists thioredoxin, superoxide dismutase, peroxiredoxin and ferritin as components of schistosome eggs. Further, those authors showed significant variation in expression levels of these molecules in immature (isolated from worms in culture) and mature eggs (isolated from faeces) [25]. Such variation in the bio-physical properties observed https://doi.org/10.1371/journal.pntd.0008500.g005…”
Section: Discussionmentioning
confidence: 94%
“…Previously, proteomic and high resolution scanning electron microscopy have shown that the schistosome eggshell and miracidia contain divalent metal ions such as iron and copper [40][41][42], most likely incorporated in proteins such as thioredoxin-peroxidase, thioredoxin, superoxide dismutase, and iron-dependent peroxidase [25,[41][42][43]. It is, therefore, reasonable to postulate that CL emitted by S. mansoni eggs when exposed to the luminol-H 2 O 2 solution results from the reaction with these ions contained in eggshells and miracidia.…”
Section: Discussionmentioning
confidence: 99%